2017
DOI: 10.23876/j.krcp.2017.36.3.209
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of renal anemia: Erythropoiesis stimulating agents and beyond

Abstract: Anemia, complicating the course of chronic kidney disease, is a significant parameter, whether interpreted as subjective impairment or an objective prognostic marker. Renal anemia is predominantly due to relative erythropoietin (EPO) deficiency. EPO inhibits apoptosis of erythrocyte precursors. Studies using EPO substitution have shown that increasing hemoglobin (Hb) levels up to 10–11 g/dL is associated with clinical improvement. However, it has not been unequivocally proven that further intensification of er… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 94 publications
0
20
0
Order By: Relevance
“…Sotatercept is a fusion protein comprising of an extracellular chain of activin receptor IIA and the Fc domain of human IgG1. It inhibits the activation of endogenic, membranous receptors (ActRIIA) of activin by binding circulating activin and related proteins (e.g., BMP 10 and BMP 11) [104] Moreover, it influences the expression of angiotensin II which can promote erythropoiesis directly and indirectly via EPO production [105]. Sotatercept also stimulates the release of the mature erythrocyte forms, decreases the expression of the vascular endothelial growth factor (VEGF), which is an inhibitor of erythropoiesis and inhibits hepcidin transcription in the liver [106].…”
Section: New Strategies Of Anemia Treatmentmentioning
confidence: 99%
“…Sotatercept is a fusion protein comprising of an extracellular chain of activin receptor IIA and the Fc domain of human IgG1. It inhibits the activation of endogenic, membranous receptors (ActRIIA) of activin by binding circulating activin and related proteins (e.g., BMP 10 and BMP 11) [104] Moreover, it influences the expression of angiotensin II which can promote erythropoiesis directly and indirectly via EPO production [105]. Sotatercept also stimulates the release of the mature erythrocyte forms, decreases the expression of the vascular endothelial growth factor (VEGF), which is an inhibitor of erythropoiesis and inhibits hepcidin transcription in the liver [106].…”
Section: New Strategies Of Anemia Treatmentmentioning
confidence: 99%
“…Th erefore, recombinant erythropoietins-alpha (Eprex, Epobioicrine, Epostim etc.) are widely used to correct anemias in diff erent diseases and posttransplant conditions [2].…”
Section: Resultsmentioning
confidence: 99%
“…EPO is the major growth factor involved in erythropoiesis and has been used to treat renal anemia in patients with advanced CKD in clinical practice [41]. Studies have demonstrated that EPO has cytoprotective effects in many non-erythroid cells, including renal TECs, which are largely attributed to anti-apoptosis, anti-oxidant, and anti-in ammatory effects [42].…”
Section: Discussionmentioning
confidence: 99%